Chloroplast retrograde regulation of heat stress responses in plants - Ai-Zhen eSun; Fang-Qing eGuo (Frontiers in Plant Science, 2016)
It is well known that intracellular signaling from chloroplast to nucleus plays a vital role in stress responses to survive environmental perturbations. The chloroplasts were proposed as sensors to heat stress since components of the photosynthetic apparatus housed in the chloroplast are the primary susceptible targets of thermal damage in plants. Thus, communicating subcellular perturbations to the nucleus is critical during exposure to extreme environmental conditions such as heat stress. By coordinating expression of stress specific nuclear genes essential for adaptive responses to hostile environment, plants optimize different cell functions and activate acclimation responses through retrograde signaling pathways. Such diverse metabolic and biosynthetic functions require efficient communication between plastids and the nucleus. In recent years several putative retrograde signals released from plastids that regulate nuclear genes have been identified and signaling pathways have been proposed. In this review, we provide an update on retrograde signals derived from tetrapyrroles, carotenoids, reactive oxygen species (ROS) and organellar gene expression (OGE) in the context of heat stress responses and address their roles in retrograde regulation of heat-responsive gene expression, systemic acquired acclimation and cellular coordination in plants.